Deactivation of Palladium Electrocatalysts for Alcohols Oxidation in Basic Electrolytes. (20th September 2015) - Wang, Lianqin; Lavacchi, Alessandro; Bellini, Marco; D'Acapito, Francesco; Benedetto, Francesco Di; Innocenti, Massimo; Miller, Hamish A.; Montegrossi, Giordano; Zafferoni, Claudio; Vizza, Francesco
Highlights: Pd catalysts deactivates in the alkaline electro-oxidation of alcohols. Deactivation is related to the anodic stress of catalyst. Catalyst deactivation is ascribed to the oxidation of Pd. Catalyst service life can be improved by a suitable choice of operating conditions. Abstract: Deactivation is one the main causes still preventing the full exploitation of palladium electrocatalysts in alkaline direct alcohol fuel cells and the electrochemical reforming of alcohols. While often attributed to the adsorption of poisoning species generated in the alcohols oxidation, in the present work we demonstrate that deactivation is provoked by the formation of palladium oxides. A combined approach including i) fuel cell runs, ii) cyclic voltammetry and iii) near edge X-ray absorption spectroscopy has enabled us to draw the conclusions reported in the paper.